(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Spiritual intelligence alludes to the aptitudes, capacities and practices required to comprehend one’s internal identity including contemplations, beliefs, values and activities, to keep up a feeling of having a place with others, to express reliance on incomparable power through reflection, to live with a psyche of request and a journey for meaning in life, and to act in adoration and sympathy. The present research paper expected to consider the spiritual intelligence among secondary school students concerning sex and school management.Spiritual intelligence instrument created by the specialist was utilized for the present examination. For statistical examination and hypothesis testing, Mean and F-test was connected. The discoveries uncover that girls have high spiritual intelligence than boys. Assist discoveries additionally demonstrated a noteworthy distinction between the scores of spiritual intelligence concerning school management.